Social work practice : a competency-based approach - Poulin, John E.; Matis, Selina (Springer Publishing Company, 2021)
"This primary social work practice text, built around the nine core 2015 CSWE competencies, is the only book available that provides students with the benefits of a fully integrated competency-based approach. The book immediately immerses students in the competencies required for social work practice at the micro, mezzo and macro levels. Designed for use in both upper level BSW and foundation level MSW social work practice courses, the book is uniquely structured to deliver the knowledge and skills students need to develop mastery of the professional social work competencies"--